Stress-induced multiple organ damage in rats is ameliorated by the antioxidant and anxiolytic effects of regular exercise - YEGEN, BERRAK; ERCAN, FERİHA; KASIMAY ÇAKIR, ÖZGÜR (WILEY, 2010)
Our aim was to investigate the effects of moderate load, regular swimming exercise on stress-induced anxiety, and associated oxidative organ injury. Male Sprague-Dawley rats (n = 48) were either kept sedentary or submitted to swimming exercise for 8 weeks. Rats were then divided as non-stressed, acute stress, and chronic stress groups. After acute or chronic stress (electric foot shocks) applications, rats were placed on a holeboard and the exploratory behavior was recorded to assess the anxiety. Rats were decapitated after the stress application. Acute and chronic stress induction led to increased serum cortisol levels as compared to non-stressed groups. Plasma aspartate aminotransferase levels that were elevated in sedentary rats with both stress exposures were lower in trained rats. Malondialdehyde levels and myeloperoxidase activity were increased in the cardiac muscle, liver, stomach, and brain of the stressed rats with a concomitant reduction in the glutathione levels, while stress-induced changes in malondialdehyde, myeloperoxidase, and glutathione levels were reversed in the trained animals. Exercise, which led to increased malondialdehyde and reduced glutathione levels in the skeletal muscle of the non-stressed rats, also protected against stress-induced oxidative damage. Regular exercise with its anxiolytic and antioxidant effects ameliorates stress-induced oxidative organ damage by a neutrophil-dependent mechanism. Copyright (C) 2010 John Wiley & Sons, Ltd.
Keywords: swimming; stress; myeloperoxidase; antioxidant; malondialdehyde; INDUCED OXIDANT STRESS; PHYSICAL-EXERCISE; VITAMIN-E; OXIDATIVE STRESS; SKELETAL-MUSCLE; DIETARY SUPPLEMENTATION; TISSUE-DAMAGE; FREE-RADICALS; ENDURANCE; INFLAMMATION